Análisis funcional de la expresión génica obtenida por transcriptómica de células madre de la papila dental estimuladas con láser de baja potencia (2023)
Introduction. The application of LLLT low power laser is a therapy that has been used in different health applications, including in dentistry to reduce inflammation, pain control, tissue regeneration stimulation, among others. Although in orthodontics it is used during treatment with fixed appliances to accelerate the bone remodeling process, the underlying molecular bases that govern this process are unknown.